All Solid-State Lithium–Sulfur Battery Using a Glass-Type P2S5–Li2S Electrolyte: Benefits on Anode Kinetics. Issue 4 (1st January 2015) - Yamada, Takanobu; Ito, Seitaro; Omoda, Ryo; Watanabe, Taku; Aihara, Yuichi; Agostini, Marco; Ulissi, Ulderico; Hassoun, Jusef; Scrosati, Bruno
Abstract : Lithium-sulfur (Li-S) batteries are promising candidates for next generation electrical energy storage devices due to their high specific energy. Despite intense research, there are still a number of technical challenges in developing a high performance Li-S battery. To elucidate the issues, an all solid-state Li-S battery was fabricated using Li3 PS4 solid electrolyte. Most of the theoretical capacity of sulfur, 1600 mAhg −1 was attained in the initial discharge-charge cycles with a high coulombic efficiency approaching 99%. To verify the benefit of the solid state electrolyte, galvanostatic stripping-deposition tests were also carried out on a symmetrical Li/Li cell and compared with those of a liquid electrolyte (1 M- lithium bis(trifluoromethane sulfonyl) imide (LiTFSI) in a mixture of 1, 3-dioxolane (DOL)-diethoxyethane (DEE)). The kinetics and thermodynamics of the solid-state cell are discussed from the viewpoint of the charge transfer processes. This study demonstrates both the merits and drawbacks of using the solid sulfide electrolyte in a Li-S battery and facilitates the further improvement of this important high energy storage device.